The Effect of Good Corporate Governance on The Profitability of Mining Companies Listed on The Indonesia Stock Exchange - Suherman Suherman; Mohamad Adam; Marlina Widiyanti; Yuliani Yuliani (Jurnal Syntax Transformation, 2024)
The aim of this research is to obtain empirical evidence regarding the influence of management ownership, institutional ownership, independent ownership boards, audit committees on profitability (Return On Equity) in companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained were 15 companies for the 2019-2022 period so there were 60 analysis units. The research design is quantitative descriptive. The analysis technique in this research uses the panel data regression method. The research results show that management ownership, independent board ownership, and audit committee have no effect on profitability. Meanwhile, institutional ownership has a significant negative effect on profitability. The implication of this research is that companies must pay attention to institutional ownership shares, because they can have a negative impact on the company's profitability.